2021
DOI: 10.2337/dc20-2676
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Overweight/Obesity Are Independent, Nonadditive Risk Factors for In-Hospital Severity of COVID-19: An International, Multicenter Retrospective Meta-analysis

Abstract: Obesity is an established risk factor for severe coronavirus disease 2019 , but the contribution of overweight and/or diabetes remains unclear. In a multicenter, international study, we investigated if overweight, obesity, and diabetes were independently associated with COVID-19 severity and whether the BMIassociated risk was increased among those with diabetes. RESEARCH DESIGN AND METHODSWe retrospectively extracted data from health care records and regional databases of hospitalized adult patients with COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 36 publications
2
44
1
6
Order By: Relevance
“…A meta‐analysis has observed that the risk of obesity and diabetes is independent and non‐additive between them in COVID‐19 patients. 12 These data would suggest that our results are more related to the presence of obesity rather than other comorbidities. In agreement with this hypothesis, the multivariate analysis found that obesity was independently associated with a greater number of post‐COVID symptoms and poor sleep quality.…”
Section: Discussionmentioning
confidence: 80%
“…A meta‐analysis has observed that the risk of obesity and diabetes is independent and non‐additive between them in COVID‐19 patients. 12 These data would suggest that our results are more related to the presence of obesity rather than other comorbidities. In agreement with this hypothesis, the multivariate analysis found that obesity was independently associated with a greater number of post‐COVID symptoms and poor sleep quality.…”
Section: Discussionmentioning
confidence: 80%
“…Firstly, all data was derived from a small sample cohort derived from a single study site, including unbalanced patient versus control groups, and it remains to be determined how much these data can be extrapolated to other patient populations. Importantly, future studies with a larger number of patients should include an equal number of males and females as male sex is independently associated with increased COVID-19 severity [ 40 ]. Furthermore, additional studies are required across a broader range of patients ( i.e.…”
Section: Discussionmentioning
confidence: 99%
“…4 8 12 14 It is now well documented that people with hypertension, obesity and other metabolic disturbances have increased risk of to severe COVID-19 infections. [50][51][52][53][54] In a 2018 study, it was showed that the prevalence of metabolic syndrome and its components (especially that of abdominal obesity, hypertension and elevated fasting glucose level) has increased significantly in the Hungarian population in the last decade, as has the number of individuals whose hypertension and metabolic disturbances remain untreated. 55 They are also at higher risk of contracting the virus because they are more likely to be in public facing jobs, are less likely to be able to work remotely and find it more difficult to isolate if infected.…”
Section: Discussionmentioning
confidence: 99%